The Ural Population Project. Demography and Culture From Microdata in a European-Asian Border Region - Elena Glavatskaya; Julia Borovik; Gunnar Thorvaldsen (Historical Life Course Studies)
The Ural Population Project (URAPP) is built from individual level data transcriptions of 19th- to early 20th-century parish records and mid-19th-century census-like tax revisions manuscripts. This article discusses the source material, the contents, the history of creation and the strategy of the URAPP database and the outcome of the main research topics so far, including historical demography, Jewish studies, indigenous studies and studies of religious minorities in the Urals and Siberia. Our studies of the ethno-religious cultural landscape of the Urals and northwestern Siberia as well as participation in population history projects was more vital backgrounds than the traditional focus on aggregates. The over 65,000 vital events transcribed from parish records of Russian Orthodox Churches and minority religions in and around Ekaterinburg have been the basis for studies of mortality, nuptiality, religion and other characteristics. We found that the Jewish population kept their traditions and connections with relatives in the Pale of Settlement. Prisoners of WWI usually marrying within their own religious group. Infant mortality in Ekaterinburg was lower among Jews and the Catholics, minorities with higher education and western background, while the Orthodox majority exposed their newborn to extremely tough baptism. The burial records show cases of the Spanish flu in 1918–1919, but on a lower level than in the West, supporting recent theories that estimates of flu mortality may be too high. Based on the tax revisions, polygyny was officially recognized among the indigenous Siberian people. The strategy of the URAPP project has evolved from transcribing microdata about minorities towards covering the whole population.